Red pomegranate (Punica granatum L.) peel extract mud mask formulation and tyrosinase-inhibition activity test - Faizatun, Faizatun; Alfianita, Alfianita; Nafisa, Safira (Faculty of Pharmacy, Universitas Pancasila, 2024)
The peel of red pomegranates (Punica granatum L.) contains gallic acid and ellagic acid, which inhibit tyrosinase, an enzyme that aids melanin formation. This study aimed to determine how variations in the concentration of kaolin base affected the evaluation outcomes of mud mask formulations containing P. granatum fruit peel extract. P. granatum fruit peel extract was used in 3 formulas with variations in the kaolin base concentration of 19.5%, 22.5%, and 26.3%. The three formulations were subsequently evaluated through a series of procedures, which included organoleptic, homogeneity, spreadability, viscosity, pH measurements, and drying time. The enzyme-linked immunosorbent assay (ELISA) method was employed to determine the inhibitory activity of the tyrosinase enzyme. Formula 2 gives the best results with the characteristics of having a distinctive odor and thick brownish-green color, homogeneous preparation, spreadability of 20.5863 cm2, a viscosity of 16040 cPs; pH of 5.86, and drying time of 16.67 minutes. Inhibition of the tyrosinase enzyme by kojic acid, extracts, and preparations resulted in respective IC50 values of 31.64 μg/mL, 155.49 μg/mL, and 276.15 μg/mL. The results of the viscosity test, pH test, and mask drying time were significantly different as the concentration of the kaolin base varied (p<0.05).